1983
DOI: 10.1099/00222615-16-3-317
|View full text |Cite
|
Sign up to set email alerts
|

Proteus morgani is less frequently associated with urinary tract infections than Proteus mirabilis--an explanation

Abstract: SUMMARY. The metabolic activities of faecal and urinary strains of Proteus morgani and P. mirubilis were compared. Regardless of origin, the generation time of P. morgani strains in urine was approximately twice as long as that of the P. mirabilis strains. Urease synthesis was constitutive in P. morgani strains but required induction with urea in the P . mirabilis strains. In the presence of urea, the P. mirubilis strains liberated ammonia more rapidly and produced alkaline conditions more quickly than P. morg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…No significant differences were found between P. mirabilis and P. vulgaris in growth rates in urine and broth or in serum sensitivity. Differences in growth rates have been held responsible for differences in prevalence in urinary-tract infections of Escherichia coli and other enterobacteria (Anderson et al, 1979) and of P. mirabilis and P. morgani (Senior, 1983), but cannot account for the difference in prevalence of P. mirabilis and P. vulgaris in urinary-tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were found between P. mirabilis and P. vulgaris in growth rates in urine and broth or in serum sensitivity. Differences in growth rates have been held responsible for differences in prevalence in urinary-tract infections of Escherichia coli and other enterobacteria (Anderson et al, 1979) and of P. mirabilis and P. morgani (Senior, 1983), but cannot account for the difference in prevalence of P. mirabilis and P. vulgaris in urinary-tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…morgani are rarely associated with urinary-tract infections (Senior, 1979). This has been explained on the basis of their slow growth rate in urine and their inability to make urine alkaline rapidly (Senior, 1983). The finding that approximately half these organisms are unable to produce haemolysin suggests that such strains are at an even greater disadvantage as potential urinary-tract pathogens.…”
Section: B W Senior a N D C Hughesmentioning
confidence: 99%
“…However, other members of the tribe Proteeae are rarely associated with urinary-tract infections and some are more often associated with diarrhoea (Senior, 1979(Senior, , 1983Senior and Leslie, 1986). Since Peerbooms et al (1983) have shown that the haemolysins produced by P. mirabilis influence the virulence of this organism for the mouse, we have investigated the frequency and characteristics of haemolysin production in clinical isolates of this and all other species in the Proteeae to see if the virulence of P. mirabilis for the urinary tract is likely to be similarly linked to haemolysin production.…”
Section: Introductionmentioning
confidence: 99%
“…Proteus vulgaris and also M . morganii are a common cause of opportunistic, particularly nosocomial infections in humans [30,311. A high incidence of hemolytic strains has been reported amongst extraintestinal M. morganii isolates, and a markedly higher virulence in three animal models was observed for hemolytic strains [32].…”
mentioning
confidence: 99%